1994
DOI: 10.1037/0735-7044.108.2.294
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of subdivisions of the medial prefrontal cortex in learned cardiac adjustments in rabbits.

Abstract: Electrical stimulation of area 24 and area 32 of the medial prefrontal cortex (mPFC) in rabbits elicited increases in respiration rate and decreases in heart rate (HR) and blood pressure. However, stimulation in area 25 elicited pressor responses and a biphasic HR response consisting of an initial HR increase followed by an HR decrease. Administration of an alpha-adrenergic receptor antagonist eliminated the pressor response and bradycardiac response produced by area 25 stimulation but it had no effect on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
89
2
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(101 citation statements)
references
References 41 publications
9
89
2
1
Order By: Relevance
“…Our results contradict this presumption. The study of Powell et al [42] points also in the direction of a functional heterogeneity between areas 24, 32 and 25.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our results contradict this presumption. The study of Powell et al [42] points also in the direction of a functional heterogeneity between areas 24, 32 and 25.…”
Section: Discussionmentioning
confidence: 94%
“…According to Powell et al [42] this area is involved in autonomic conditioned responses, such as conditioned bradycardia. Similarly, Terreberry and Neafsey [50] call the medial prefrontal cortex a visceral motor region.…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies employing traditional Pavlovian conditioning paradigms have shown that aversively conditioned stimuli can evoke learning-related changes in neuronal activity within prelimbic and cingulate areas of the mPFC Peterson 1986;Powell et al 1996), and increase dopamine and serotonin efflux in these regions (Wedzony et al 1996;Yoshioka et al 1995Yoshioka et al , 1996. Lesions of the mPFC also can disrupt Pavlovian conditioned responses to sucrose or foot-shock related stimuli (Bussey et al 1997;McLaughlin and Powell 1999;Powell et al 1994). Studies of conditioned drug effects have further shown that cocaine-related stimuli can increase serotonin efflux and stimulate the expression of Fos-related proteins within the mPFC in rats (Brown and Fibiger 1992;Carey and Damianopoulos 1994;Franklin and Druhan 2000;Neisewander et al 2000), whereas lesions of this region interfere with the development of conditioned preferences for a cocaineassociated environment and with the expression of cocaine-induced sensitization effects that depend heavily on contextual conditioning (Isaac et al 1989;Pierce et al 1998;Tzschentke and Schmidt 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have investigated the role of the PFC in classical (pavlovian) conditioning. For example, several studies have demonstrated that the medial PFC (mPFC) is intimately involved in the acquisition of pavlovian-conditioned autonomic responses (Buchanan and Powell, 1982;Buchanan et al, 1985;Neafsey, 1991, 1994;Powell et al, 1994), but other studies have shown that mPFC damage has no effect on simple somatomotor eyeblink (EB) classical conditioning (Buchanan and Powell, 1982;Weible et al, 2000;McLaughlin et al, 2002;Powell et al, 2005). However, it has also been reported that, under conditions that are less than optimal for learning to occur, such as during trace conditioning or partial reinforcement, mPFC lesions also impair EB conditioning (Kronforst-Collins and Disterhoft, 1998;Weible et al, 2000;McLaughlin et al 2002;Powell et al, 2005).…”
Section: Introductionmentioning
confidence: 99%